Kategoryzacja i prototypizacja w polu semantycznym niepełnosprawności fizycznej - Prażmowska-Bartoszek, Katarzyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
This article is an attempt to gather and describe lexis pertaining to people with physical disabilities which has been excerpted from selected dictionaries of the Polish language. The aim of the article is to formulate answers to the question of how Polish language users speak of the physically disabled, what the character of the words and expressions is and for what purpose they are used in different communication situations (features of the discourse on physical disability in the light of dictionary analysis). The article contains a review of definitions of disability and a person with a disability which exist in medical, legal, pedagogical and linguistic sciences. It also deals with the basic assumptions in prototype semantics which is the methodological basis of the studies conducted. The collected lexems and word connections have been analysed in terms of semantics and structure.